Penerapan Nusantara Kartu Sebagai Buku Ajar IPS di Kelas 3 SDN Sungai Miai 4 - Salsabela Ashlin; Ayuni Ayuni; Mina Zuyyina Ramadhani; Aldy Ferdiyansyah; Asniwati Asniwati (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
Abstract, Learning media is very useful, especially in improving students' understanding of concepts, strengthening their retention, and fostering their interest in learning. This study uses a descriptive qualitative approach to understand the problem of limited social studies learning media in grade 3 of SDN Sungai Miai 4 and find relevant solutions. Nusantara Kartu is an innovation in learning media designed to introduce and foster students' appreciation of the diversity of Indonesian culture. Nusantara Kartu media has a physical form like a medium-sized card, printed in color, and equipped with pictures and brief information about cultural elements in Indonesia. Nusantara Kartu media is able to overcome the problem of limited textbooks and student boredom in social studies learning. This media not only creates a fun and meaningful learning atmosphere, but also increases students' active participation and understanding of the diversity of Indonesian culture. Teachers can start trying to create similar media that suits the needs of each class.